Etnomatematika pada Rombong Gula Gending dalam Aktivitas Pembelajaran Matematika - Munir, Muhammad; Sholehah, Hijriati (Jurnal al Muta'aliyah: Pendidikan Guru Madrasah Ibtidaiyah, 2023)
Abstract This research was conducted using elements of mathematics or known as the ethnomathematics approach. Ethnomatematics is one of the approaches used in culture-based mathematics learning. This study used a qualitative research method with an ethnographic approach. The data used are data obtained from literature, observation, and documentation. The data generated in this study is that there are elements of mathematics (ethnomathematics) in the gending sugar troupe, namely geometric shapes (tubes and trapeziums) and flat planes (circles and rectangles). cultural elements can be used as one of the media for learning mathematics.